Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1097/01.asn.0000025781.16723.68
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Calcium-Sensing Receptor Mutation in Severe Autosomal Dominant Hypocalcemia with a Bartter-Like Syndrome

Abstract: Abstract. The extracellular Ca 2ϩ -sensing receptor (CaSR) plays an essential role in extracellular Ca 2ϩ homeostasis by regulating the rate of parathyroid hormone (PTH) secretion and the rate of calcium reabsorption by the kidney. Activation of the renal CaSR is thought to inhibit paracellular divalent cation reabsorption in the cortical ascending limb (cTAL) both directly and indirectly via a decrease in NaCl transport. However, in patients with autosomal dominant hypocalcemia (ADH), caused by CaSR gain-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
196
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(200 citation statements)
references
References 32 publications
(33 reference statements)
2
196
1
1
Order By: Relevance
“…49 These second messengers (inositol 1,4,5-trisphosphate and intracellular Ca ++ ) have been broadly used to assess the genetic mutations of CaSR in Xenopus oocytes and HEK293 cells. [15][16][17][18] Our study has revealed a novel second messenger based on miRs that is particularly useful for assessing the activating mutations of CaSR found in ADH disease. The common ADH mutations invariably repress the transcription of miR-9 and miR-374 genes, which can be relieved by HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…49 These second messengers (inositol 1,4,5-trisphosphate and intracellular Ca ++ ) have been broadly used to assess the genetic mutations of CaSR in Xenopus oocytes and HEK293 cells. [15][16][17][18] Our study has revealed a novel second messenger based on miRs that is particularly useful for assessing the activating mutations of CaSR found in ADH disease. The common ADH mutations invariably repress the transcription of miR-9 and miR-374 genes, which can be relieved by HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…Knowing that miRs are an important second messenger of CaSR signaling, 9 we asked whether CaSR mutations deregulated miR abundance as a potential causal mechanism and whether HDAC inhibitors corrected the CaSR mutational effects as a novel therapeutic approach for ADH disease. We generated three common ADH mutations in the human CaSR gene (E127A, F128L, and T151M previously described by Pollak et al 15 and Pearce et al 16 ), transfected the wild-type CaSR gene and its mutants into a well established cell model for studying CaSR signaling (HEK293 cells that expressed no endogenous CaSR), 17 and quantified the transcriptional levels of four miR genes-miR-9-1, miR-9-2, miR-9-3 (all three loci transcribing mature miR-9 hairpin sequence), and miR-374. Among them, the miR-9-1 and miR-374 genes were transcriptionally suppressed by the CaSR mutants.…”
Section: Hdac Inhibitors Correct Casr Mutational Effects In Adh Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, activating CaR mutations result in autosomal dominant hypocalcemia (10,11). The latter may be sometimes associated with hypercalciuria and a Bartter-like syndrome (12,13), explained by the fact that the CaR is also expressed by epithelial cells of Henle's loop. Corresponding phenotypes have been reproduced in genetically modified animal models.…”
Section: Ntracellular Camentioning
confidence: 99%
“…Gain-of-function mutations in the CASR gene have been reported in some patients with Bartter syndrome associated with hypocalcaemia and hypercalciuria. Studies showed that these mutations result in receptor activation that is more severe than other gain-of-function mutations [3] . We describe a case of adultonset Bartter syndrome with hypocalcaemia severe enough to cause osteomalacia.…”
Section: Introductionmentioning
confidence: 99%